A heat shock operon in Coxiella burnetti produces a major antigen homologous to a protein in both mycobacteria and Escherichia coli. - Vodkin, M H (1988)
A gene library from the DNA of Coxiella burnetii has been constructed in the cosmid vector pHC79. A particular clone, pJB196, reacted strongly with Coxiella-specific antibodies elicited in a number of different species of animals. This clone produced two abundant C. burnetii-specific polypeptides, a 14-kilodalton nonimmunoreactive protein and a 62-kilodalton immunoreactive protein. Sequencing identified two open reading frames, encoding polypeptides of 10.5 and 58.3 kilodaltons. The only transcriptional control element observed on the 5' side of the initiation codon resembled a heat shock promoter. This heat shock promoter was functionally regulated in Escherichia coli, since both proteins were produced by growth conditions at 37 degrees C and neither protein was detected at 23 degrees C. There were four sequences from the literature that were highly homologous (greater than 50%) to the 62-kilodalton protein from C. burnetii. Three were from Mycobacterium species and represent the immunodominant antigen of this genus. The other was from E. coli, detected as a gene that complements or suppresses a temperature-sensitive RNase activity. Since the recombinant protein was immunogenic, it may serve as an efficacious vaccine against C. burnetii and other pathogenic microorganisms that express the conserved antigen.